Genome-wide transcriptional changes in type 2 diabetic mice supplemented with lotus seed resistant starch. (30th October 2018) - Wang, Qi; Zheng, Yafeng; Zhuang, Weijing; Lu, Xu; Luo, Xianliang; Zheng, Baodong
Highlights: Lotus seed RS exhibited hypoglycemic effect in type 2 diabetic mice. The genome-wide expression patterns in pancreatic tissue were analyzed. 511 differentially expressed genes were identified. The molecular mechanism of its hypoglycemic effect was discussed. Abstract: Resistant starch has been studied extensively for its hypoglycemic activity, while its underlying molecular mechanism is not fully understood. In this study, we investigated the hypoglycemic effect of different doses of lotus seed resistant starch (LSRS) supplementation on type 2 diabetic mice and elucidated the molecular basis of its hypoglycemic effect. LSRS supplementation significantly reduced blood glucose level by 16.0%–33.6%, recovered serum insulin level by 25.0%–39.0% and improved lipid metabolism disorder in the diabetic mice. The genome-wide expression patterns in pancreatic tissue were analyzed, and 511 differentially expressed genes (DEGs) were identified. The analysis results of gene ontology (GO) functions and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways indicated that the protective effect of LSRS supplementation was most likely driven by modulating expression levels of various key factors involved in insulin secretion, insulin signal transmission, cell apoptosis, antioxidant activity and p53 signaling pathways.